Load Balancing In Mobile Cloud Computing: A Review - Arun, C; Prabu, K (International Journal of Computer Sciences and Engineering, 2018)
cloud computing is said to be the next big boom technology in IT industry infrastructure. It is claimed that it provides new levels of efficiency, flexibility and cost savings of the resources that are used in industries. Mobile Cloud Computing (MCC) is applications, Internet-based data, and related services accessed via smartphones, laptop computers, tablets and other portable devices. By using MCC, the processing and the storage of intensive mobile device jobs will take place in the cloud system and the results will be back to the mobile device. But the mobile cloud computing have some issues like power consumption, bandwidth, mobility and security. Using the mobile devices for accessing the cloud it needs an efficient load balancing technique for offloading the data to the users. In this paper, there is a detailed review on different load balancing techniques which are existing model in cloud analyst tool and some policies by different authors.